Mental health services for mood disorder outpatients in Milan during COVID-19 outbreak: The experience of the health care providers at San Raffaele hospital. (October 2020) - Franchini, Linda; Ragone, Nicola; Seghi, Federico; Barbini, Barbara; Colombo, Cristina
Abstract: The spread of COVID-19 throughout Italy, particularly Lombardy, led to adopt quarantine measures, known to exacerbate pre-existing psychiatric conditions. We described a telephone-based surveillance on 101 euthymic Mood Disorder outpatients in Milan by a non-standardized survey to evaluate reactions to lockdown measures and the presence of quarantine stressors. Frustration was the most represented quarantine stressor. Being jobless was significantly related to the presence of frustration, somatization, increased alertness, psychic anxiety and low mood; younger age to the presence of psychic anxiety, alertness and financial concerns. No recurrences were observed at the time of writing.